The Definition of Covert Intelligence and the Examination of Its Efficiency - Csizner, Zoltán (Magyar Rendészet, 2022)
The exploration of the dreaded secrets of others, the collection of secret information and intelligence have been present in human communities since ancient times. Acquiring knowledge protected from unauthorised access has, over time, become a monopoly of a society organised into a state, and its implementation has been constrained by strict legislation. However, in addition to legitimacy, an equally important feature of covert intelligence is efficiency, which shows the relationship between the resources expended and the results achieved. How can their components be defined in an abstract way, can general criteria be named, and how can the results be measured and compared? The study seeks to answer these questions, which is a key part of research examining the relationship between the effectiveness and legitimacy of covert intelligence. It is also essential to present a complex and intricate system that helps to understand the regulation of covert intelligence and the organisations responsible for its implementation.